Proceedings of the 2nd International Conference on Accounting, Management, and Economics 2017 (ICAME 2017) 2017
DOI: 10.2991/icame-17.2017.7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Work Environment And Organizational Culture On Employees' Performance Through Job Satisfaction As Intervening Variable At State Electriciy Company (Pln) Of South Makassar Area

Abstract: The work environment is the important part of a company to improve

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
2
9
0
3
Order By: Relevance
“…In line with the opinions of experts, where according to Syahrum et al, (2016), Hardiyono (2017) & Khuzaeni et al, (2013 stated that organizational culture can influence the results of employee performance. Therefore the organization must form a culture that is suitable for its employees.…”
Section: Introductionmentioning
confidence: 63%
“…In line with the opinions of experts, where according to Syahrum et al, (2016), Hardiyono (2017) & Khuzaeni et al, (2013 stated that organizational culture can influence the results of employee performance. Therefore the organization must form a culture that is suitable for its employees.…”
Section: Introductionmentioning
confidence: 63%
“…No culture is most superior in implementation in organizations because cultural suitability depends on the function and achievement of organizational goals [39]. Organizational culture has a role in creating efficiency and effectiveness of employees' work [40]. Based on the opinion of several researchers, the researcher concluded that organizational culture (OC) is a habit in the organization that has been going on for generations and has value in solving problems with indicators as value sharing, problem-solving, working together, receiving a new value, and the seriousness of achieving common goals.…”
Section: B Organizational Culturementioning
confidence: 99%
“…Personality as the stable patterns of behavior and consistent internal states that determine how an individual reacts to and interacts with others [19]. Job satisfaction is essentially an individual thing; each person will have a level of satisfaction that is not the same as the value system that applies to him [20,21]. Job Satisfaction is an essential component for employee motivation and encouragement towards better performance [22].…”
Section: Issn: 2089-9823 mentioning
confidence: 99%